2018
DOI: 10.1007/s11224-018-1177-2
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of N2 ligands to lanthanum: the complexes La (N2)1–8

Abstract: The structures and bonding properties of La(N 2 ) x (x = 1-8) complexes were investigated by density functional theory (DFT) computations using the B3LYP exchange-correlation functional in conjunction with a quasi-relativistic pseudopotential for La. The quality of the DFT electronic structures was confirmed in selected cases by relativistic multireference calculations using CASPT2 theory. From the end-on and side-on dinitrogen coordination modes in general, the structures with end-on coordination were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
23
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(33 citation statements)
references
References 53 publications
(103 reference statements)
8
23
2
Order By: Relevance
“…Indeed, test calculations in the previous study on La(N 2 ) x complexes indicated several orbitals with negligible populations and concluded on the proper performance of the 7e/10o and 11e/12o active spaces for La(N 2 ) and La(N 2 ) 2 , respectively. [29] Analogously, in the present study, the active spaces of 7e/10o and 11e/12o were used for Lu(N 2 ) and Lu(N 2 ) 2 , respectively, including the 6s and all the 5d orbitals of Lu. The contribution of the main electron configuration to the wavefunction was 84% in 2 Lu(N 2 ) 2 , while it was over 92% in the other three Lu(N 2 ) x (x = 1, 2) species.…”
Section: Casscf Calculations For the Assessment Of Multiconfiguratimentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, test calculations in the previous study on La(N 2 ) x complexes indicated several orbitals with negligible populations and concluded on the proper performance of the 7e/10o and 11e/12o active spaces for La(N 2 ) and La(N 2 ) 2 , respectively. [29] Analogously, in the present study, the active spaces of 7e/10o and 11e/12o were used for Lu(N 2 ) and Lu(N 2 ) 2 , respectively, including the 6s and all the 5d orbitals of Lu. The contribution of the main electron configuration to the wavefunction was 84% in 2 Lu(N 2 ) 2 , while it was over 92% in the other three Lu(N 2 ) x (x = 1, 2) species.…”
Section: Casscf Calculations For the Assessment Of Multiconfiguratimentioning
confidence: 99%
“…Ln interaction) resulting in positive charges of the Ln donors. [29,30] The following general observations can be made on the basis of Table 1: 1. In contrast to the analogous structures found generally in organometallic complexes across the Ln row, [66,67] there are some differences in the structures of the Ln(N 2 ) x complexes.…”
Section: Optimized Structuresmentioning
confidence: 99%
See 3 more Smart Citations